2008
DOI: 10.1142/s0218339008002666
|View full text |Cite
|
Sign up to set email alerts
|

Two Dynamic Models About Rabies Between Dogs and Human

Abstract: Our models characterize the transmission dynamics of rabies between human and dogs. Firstly, we build an ODE model to represent the natural spreading of rabies in dogs and human. We get the basic reproductive number R0 and the global stability for both the disease-free equilibrium and the endemic equilibrium. Then, we build a controlling model for rabies. We compare the efficiency of three strategies for controlling the rabies: culling, vaccination, culling and vaccination, and get controlling thresholds for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…An ordinary differential equation model was used to characterize the transmission dynamics of rabies between humans and dogs by [21,22]. The work by Zinsstag et al [23] further extended the existing models on rabies transmission between dogs to include dogto-human transmission and concluded that human postexposure prophylaxis (PEP) with a dog vaccination campaign was the more cost effective in controlling the disease in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…An ordinary differential equation model was used to characterize the transmission dynamics of rabies between humans and dogs by [21,22]. The work by Zinsstag et al [23] further extended the existing models on rabies transmission between dogs to include dogto-human transmission and concluded that human postexposure prophylaxis (PEP) with a dog vaccination campaign was the more cost effective in controlling the disease in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Carroll et al [11] created a continuous compartmental model to describe rabies epidemiology in dog populations and explored three control methods: vaccination, vaccination plus fertility control, and culling. Wang and Lou [96] and Yang and Lou [109] used ordinary differential equation models to characterize the transmission dynamics of rabies between humans and dogs. Zinsstag et al [117] extended existing models on rabies transmission between dogs to include dog-to-human transmission and concluded that combining human PEP with a dog-vaccination campaign is more cost-effective in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of which control strategy is most effective depending on the disease and its epidemiological characteristics. For most directly transmissible diseases, culling or vaccination alone has been shown to be more appropriate, whereas for others, a combination of both methods is the most optimal strategy . For our model, culling is related with mortality rate, birth rate, density‐dependent reduction in birth rate, loss of resistance, and the transmission coefficient whereas vaccination will directly influence the recovery rate and the transmission rate.…”
Section: Numerical Simulationsmentioning
confidence: 99%